2001
DOI: 10.1002/1521-3870(200108)47:3<423::aid-malq423>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-constructive Properties of the Real Numbers

Abstract: We study the relationship between various properties of the real numbers and weak choice principles.Mathematics Subject Classification: 03E25, 04A25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…By mimicking the proof of the claim we can also show that for all n, m ∈ k, if B n ∩ B m = ∅, then C n = C m , where C n , C m are given by (1). Define now a relation ∼ on k by requiring for all n, m ∈ k, n∼m iff C n = C m .…”
Section: (I) ⇒ (Iii) Fix a And B As In (Iii) For Each I ∈ K Letmentioning
confidence: 88%
“…By mimicking the proof of the claim we can also show that for all n, m ∈ k, if B n ∩ B m = ∅, then C n = C m , where C n , C m are given by (1). Define now a relation ∼ on k by requiring for all n, m ∈ k, n∼m iff C n = C m .…”
Section: (I) ⇒ (Iii) Fix a And B As In (Iii) For Each I ∈ K Letmentioning
confidence: 88%
“…(10) In [6] we showed that Form 203 implies Form 170, and by (8) we deduce that Form 203 implies Form 169. The implication "Form 203 ⇒ Form 212" has been proved in [10].…”
mentioning
confidence: 90%
“…(6) In M5(ℵ), CC(R) is true, whereas Form 169 fails, see [7]. The second assertion of (6) has been proved in [10,Proposition 8]. …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…£ Example 1 demonstrates explicitly the fact that the most fundamental questions concerning Lindelöf (compact) metric spaces can be undecidable from the Zermelo-Frankel axioms of set theory alone. More examples of the counter-intuitive behavior of metric spaces, in absence of AC, can be found in [2,6,3,4,14,12,13,15,8,9,10].…”
Section: Introductionmentioning
confidence: 99%